Peritoneal cytological diagnosis and cell differentiation through immunocytology Zytologische befundsicherung durch immunologische zelldifferenzierung im peritonealen ergussmaterial - Schubert, J.; Vieth, M. (Verdauungskrankheiten, 2010)
The history of cytology of serous cavities dates back to the end of the 19th century. Already at that time it was obvious that it is problematic to differentiate reactive mesothelial proliferation from tumor cells. This is still a problem today. Diagnostics cavity fluids belongs to the most complicated field in clinical cytology. Today further methods like immunocytology are available. For a sufficient diagnosis the correct aspiration of material is very important. © 2010 Dustri-Verlag Dr. Karl Feistle.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Cytological diagnosis; Immunocytological cell differentiation; Peritoneum